Pengaruh Integritas dan Moralitas Individu pada Kecurangan Akuntansi dengan Sistem Pengendalian Internal sebagai Variabel Mediasi - Yogi Anggara, I Kadek; Bambang Suprasto, Herkulanus (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of integrity and morality of individuals on accounting fraud with internal control systems as a mediating variable. The population in this study are 37 Regional Organizations in Badung. Determination of the sample using purposive sampling with 74 respondents. The results showed that individual integrity and morality had a negative effect on accounting fraud, integrity and morality of individuals had a positive effect on the internal control system and the internal control system had a negative effect on accounting fraud. Internal control system partially mediates the negative effect of Integrity on accounting fraud. Internal control system does not mediate the negative effect of Individual Morality on Accounting Fraud. The results are expected to be able to provide insight for relevant parties to pay more attention to internal control systems because they can influence mediating integrity against accounting fraud. Keywords: Cheating; Aaccounting Fraud; Regional Organizations.